2015
DOI: 10.5301/ijao.5000414
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Factors Associated with Achievement of High-Volume Post-Dilution Hemodiafiltration: Results from An International Study

Abstract: Dialysis center policy in terms of blood flow, treatment time, filter size, and perhaps even hemoglobin targets plays a key role in achieving high-volume HDF. All of these are modifiable factors that can help in prescribing an optimal combination of dialyzer size, achievable blood flows, and treatment times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 22 publications
(39 reference statements)
1
23
0
3
Order By: Relevance
“…Standardized b expresses how much substitution volume changes when that independent variable changes by 1 SD and thus it conveys the relative importance of the different variables. Most other studies have used a constant dialysate flow, not analyzed the effect, or used much slower dialysate flows than used in our patient cohort (11,23,26). However, we also observed that individual parameters, such as lower serum albumin, higher CRP, greater anticoagulation dose requirement, diabetes, and overall comorbidity resulted in lower substitution volume exchanged.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Standardized b expresses how much substitution volume changes when that independent variable changes by 1 SD and thus it conveys the relative importance of the different variables. Most other studies have used a constant dialysate flow, not analyzed the effect, or used much slower dialysate flows than used in our patient cohort (11,23,26). However, we also observed that individual parameters, such as lower serum albumin, higher CRP, greater anticoagulation dose requirement, diabetes, and overall comorbidity resulted in lower substitution volume exchanged.…”
Section: Discussionmentioning
confidence: 69%
“…As patients usually have greater weight gains with the longer weekend gap between dialysis sessions, and, therefore, greater ultrafiltration requirements, this may explain previous reports of lower convective exchanges with the first OL-HDF session of the week compared to the last session, in terms of less substitution fluid, but more ultrafiltration (23). As such some previous studies have reported a reduction in convective exchange with increasing hematocrit (11,26). Convection is driven by hydrostatic pressure and as such is dependent upon blood flow.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…), others mainly defined by patient characteristics , that is, extracorporeal blood flow. Blood flow is one of the most important factors associated with adequacy not only in terms of low‐molecular weight substances for achieving Kt / V ( K ‐ dialyzer clearance of urea; t ‐ dialysis time; V ‐ volume of distribution of urea) but also of middle molecule clearances as it is also a driver for convective volume in postdilution hemodiafiltration.…”
Section: Summary Of the Single‐needle Phases Of A Cycle In The Equipmmentioning
confidence: 99%